Georgia Indebtedness Poverty Note Analysis Based on Integrated Household Survey - Nozaki, Natsuko Kiso (World Bank E-Library Archive, 2018)
There is considerable public concern about the level of household indebtedness in Georgia. The new regulation expected to come into force on November 1, 2018 addresses this concern by enforcing the responsible credit framework targeting commercial banks. The objective of this note is twofold. First, the note presents micro-level evidence using the nationally representative household survey to understand households' borrowing patterns with supporting evidence from perceptions surveys. Second, the note examines plausible causal effects of over-indebtedness on household's welfare. This paper is structured as follows. Section 2 provides macroeconomic indicators and findings from perception survey as the background evidence. Section 3 illustrates the prevalence of borrowing among the households and identifies type of households that borrow from different sources. Section 4 shows results from the causal impact analysis of bank loans on household welfare. Section 5 concludes with directions for future research